Emerging Trends in Human Resource Management (Trinity Journal of Management, IT & Media (TJMITM), 2015)
HRM i.e Human Resource Management is a strategic and comprehensive  approach to manage Manpower at workplace & working environment.  Earlier HRM was considered as a job responsible for the attracting, re cruiting, selecting, training, assessment and compensation of employees  while ensuring compliance with employment and labor laws. Now a days this profession is considered as a passion by youngsters as it  involves many innovations like succession planning, business continuity  planning, workforce diversity, labor relations and some aspects of merg ers and acquisitions. HRM also has impact of Global, Political, Social, Economic & techno logical trends of the society & work culture. The paper focuses on how upcoming techniques can be taken up and its  impact on different management decisions and challenges arising for the  organization etc.The paper discusses the various issues related to HRM. The paper closes  with recommendations and strategies which can be adopted by the orga nization for solving the issues.
Keywords: Human Resource; Recruitment; Trends; Innovation